Pengembangan Aplikasi Persediaan, Penjualan dan Pembelian Barang berbasis Website pada UD. Lancar Jaya Motor - Septian Dwi Cahyo; Adam Hendra Brata; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
UD. Lancar Jaya Motor is a shop that sells various auto parts in Bajulmati Village, Wongsorejo District, Banyuwangi Regency, which has been established since 2002. In carrying out his business, the owner of UD. Lancar Jaya Motor is assisted by 2 employees. Even though UD. Lancar Jaya Motor has been running its business for a very long time, but the business processes that occur are still manual. From the results of interviews with the owner of UD. Lancar Jaya Motor, found several problems in ongoing business processes. Some of the problems that occurred among others is there is no product management inventory which requires employees to record every item that runs out as a reference for the owner to make purchases from suppliers, the sales transaction process is still being carried out by writing on notes and adding up using a calculator making the transaction process less efficient and calculating store revenue which is done independently by the owner makes the working hours longer. Therefore, a solution is offered to solve the problems that have been described, one of the solutions offered is to build a web-based application. Website-based application development in this study uses the waterfall model software development method, PHP programming language with the help of the Laravel framework and MySQL database. This research produces 3 actors, 38 functional needs and 1 non-functional requirement. The website-based application that has been built has been tested in the form of unit testing which results in 100% valid in 3 test cases, validation testing which results in 100% valid on 38 functional requirements and compatibility testing which shows the application can run well on 6 web browsers.